Fertility with artificial insemination: gilts that lock on the insemination spirette vs. those that don't - W E Schmidt; Duane L Davis; Jeffrey S Stevenson (Kansas Agricultural Experiment Station Research Reports, 1982)
KSU breeding records show a higher farrowing rate for gilts that "lock" on the insemination spirette at both inseminations as opposed to gilts that "lock" at one insemination or at neither insemination. Continued research is focusing on factors affecting female response to insemination and fertility.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Artificial insemination; Insemination spirette